Induced Abortions and Contraception in Declarations and Practice of Employees of Various Factories and other Institutions of Poznań City - Augustyn, Mirosław (Anthropological Review, 1983)
Human fertility becomes still more dependent upon artificial control of conceptions and births. Increasing amount of induced abortions is, due to elements of populational policy. The most important among these elements seems to be knowledge upon methods of contraception. The present paper describes state of knowledge upon contraception and abortions among employees from the city of Poznan and practice of birth regulation among them. Furthermore, social, moral and economic determinants of declarations and practice are analysed. Results of the present study are compared with earlier data for the same population enalbling thus conclusions considering time trends and prospects for the future to be drawn. On grounds of results of the present work it may be stated that in Poland (in contrast to other developed countries) interest in “natural” methods increases. This tendency, however, is not supported by adequate access to information necessary for efficient application of “natural” methods. Another observable tendency is a decrease in application of chemical and mechanical contraceptives while no important change in amount of coitus interruptus application can be observed. There is also a change in views upon abortions and contraception toward more liberal ones, Comparison of factors modifying views and practice of birth control shows that the most important among them are creed and education (non-believers and persons with at least high school education have more liberal views than believers and less educated people) with economic factors (e.g. actual number of children in a family) strongly influencing practice of birth limitation.